IMPLIKASI KOLABORASI INTERPROFESIONAL TERHADAP LAYANAN KEPERAWATAN BERDASARKAN PERPEKTIF HOLISTIC CARE: SYSTEMATIC REVIEW - Hanna Ceria Lumbantoruan; Rika Endah Nurhidayah (Jurnal Maternitas Kebidanan, 2023)
This study aims to determine the implications of interprofessional collaboration for nursing health care ased on a holistic care perspective. The research design uses a systematic review through online databases including ProQuest, Science Direct, and Pubmed. The process of selecting articles uses the PRISMA method. The number of articles obtained was 249, then there were 31 selected articles used in this review. The results of the study indicate that well-achieved interpersonal collaboration will have a positive impact on nursing services, especially the outcomes that are perceived by patients holistically.